2012
DOI: 10.1007/s10096-012-1581-2
|View full text |Cite
|
Sign up to set email alerts
|

Severe cochlear inflammation and vestibular syndrome in an experimental model of Streptococcus suis infection in mice

Abstract: Hearing impairment is a common and frequently permanent sequel of Streptococcus suis meningitis in humans. Nevertheless, mechanisms underlying the development of cochlear damage have not been addressed so far. In the present work, we characterized a mouse model of suppurative labyrinthitis and meningitis induced by a systemic infection with S. suis and studied the impact of the injected bacterial dosage on the progression of such inflammatory events. We observed that high infection doses of bacteria lead to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…In swine, S. suis is mainly transmitted by aerosols, and airborne transmission among pigs has been clearly demonstrated (34). S. suis cells play a certain role in mixed respiratory infections, although it is not considered a primary cause of swine pneumonia (1), indicating that it also uses the respiratory tract as a transient passage before reaching the bloodstream and causing bacteremia, which is essential for the pathogen to cause meningitis (35). The actual early mechanisms used by this pathogen to interact with epithelial cells and to further invade the bloodstream are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…In swine, S. suis is mainly transmitted by aerosols, and airborne transmission among pigs has been clearly demonstrated (34). S. suis cells play a certain role in mixed respiratory infections, although it is not considered a primary cause of swine pneumonia (1), indicating that it also uses the respiratory tract as a transient passage before reaching the bloodstream and causing bacteremia, which is essential for the pathogen to cause meningitis (35). The actual early mechanisms used by this pathogen to interact with epithelial cells and to further invade the bloodstream are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…According to these authors, rather cochlear sepsis, resulting from passage of the organism from the sub-arachnoid space to the perilymph via the cochlear aqueduct, might be primarily responsible for the hearing loss complicating bacterial meningitis caused by S. suis. This view has been supported by the results obtained by Dominguez-Punaro et al [15], who observed that mice infected with a high doses of S. suis bacteria developed sustained bacteraemia, with an increase in the permeability of the blood-labyrinth and blood-brain barriers, resulting in suppurative labyrinthitis and meningitis.…”
Section: Invasion Into Deeper Tissue and Translocation In The Bloodstmentioning
confidence: 55%
“…The pathogenesis and virulence mechanisms involved in S. suis serotype 2 infections are still unclear, although a number of mouse models have been developed [6,25,26,28,29,31] and despite the fact that in vitro assays examining specific virulence mechanisms have been generated [32,33,34,35]. …”
Section: Discussionmentioning
confidence: 99%
“…A number of experimental animal models for evaluation of virulence of S. suis serotype 2 isolates have been developed in mice and pigs [25]. At present there is no standardized animal model for studying S. suis infection, and this has caused some confusion in designating strains as virulent or non-virulent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation